Genomic Resources Notes Accepted 1 June 2015 – 31 July 2015. (November 2015) - Genomic Resources Development Consortium; Álvarez, P.; Arthofer, Wolfgang; Coelho, Maria M.; Conklin, D.; Estonba, A.; Grosso, Ana R.; Helyar, S. J.; Langa, J.; Machado, Miguel P.; Montes, I.; Pinho, Joana; et al.
Abstract This article documents the public availability of (i) microbiomes in diet and gut of larvae from the dipteran Dilophus febrilis using massive parallel sequencing, (ii) SNP and SSR discovery and characterization in the transcriptome of the Atlantic mackerel (Scomber scombrus, L) and (iii) assembled transcriptome for an endangered, endemic Iberian cyprinid fish (Squalius pyrenaicus).